A Report on: Engaging Private sector actors in cocoa value chains in adopting Climate Smart Cocoa (CSC) Practices in Ghana - Dalaa, Mustapha Alasan; Hicks, Frank; Mensah, Sharon; Asare, Richard (2017)
International Institute of Tropical Agriculture (IITA) and its consortium members (Sustainable Food Lab-SFL, Root Capital-RC, Rainforest Alliance-RA and CIAT) on the Climate Change, Agriculture and Food Security (CCAFS) Flagship Project entitled, “Mainstreaming Climate Smart Value Chains “has for the past two years laid the foundation to engage the private sector in piloting new CSC recommendations. A period of diagnostics has culminated into decision support tools ready for use in the pilots in three climate impact zones delineated by the project (see map). The objective of meetings with the private sector was to scope their commitment for Climate Smart Agriculture (CSA) adoption. It was also to understand whether the private sector have on-going initiatives towards addressing the challenges of CC in the cocoa value chain. To do this, some of the private sector companies were contacted for possible collaboration with the consortium to pilot and co-learn with the implementation of the new Climate Smart Cocoa (CSC) practices with their farmers. The team that represented the consortium in the process of engaging the private sector was mainly from IITA and SFL.